Analysis of TCR Repertoire and PD-1 Expression in Decidual and Peripheral CD8+ T Cells Reveals Distinct Immune Mechanisms in Miscarriage and Preeclampsia - Morita, Keiko; Tsuda, Sayaka; Kobayashi, Eiji; Hamana, Hiroshi; Tsuda, Kei; Shima, Tomoko; Nakashima, Akitoshi; Ushijima, Akemi; Kishi, Hiroyuki; Saito, Shigeru (Frontiers in Immunology, 2020)
CD8+ T cells, the most abundant T cell subset in the decidua, play a critical role in the maintenance of pregnancy. The majority of decidual CD8+ T cells have an effector memory phenotype, while those in the peripheral blood display a naive phenotype. An increased amount of highly differentiated CD8+ T cells in the decidua indicates local antigen stimulation and expansion, albeit these CD8+ T cells are suppressed. In decidual CD8+ T cells, co-inhibitory molecules such as PD-1, TIM-3, LAG-3, and CTLA-4 are upregulated, reflecting the suppression of cytotoxicity. Previous studies established the importance of the PD-1/PD-L1 interaction for feto-maternal tolerance. CD8+ T cells could directly recognize fetal-specific antigens, such as HLA-C, expressed by trophoblasts. However, although fetal-specific CD8+ T cells have been reported, their TCR repertoires have not been identified. In this study, we analyzed the TCR repertoires of effector memory CD8+ T cells (CD8+ EM cells) and naive CD8+ T cells (CD8+ N cells) in the decidua and peripheral blood of women with normal or complicated pregnancy and examined PD-1 expression at a single-cell level to verify whether antigen-specific CD8+ T cells accumulate in the decidua and to identify immunological differences related to the suppression of antigen-specific CD8+ T cells between normal pregnancy, miscarriage, and preeclampsia. We observed that some TCRβ repertoires, which might recognize fetal or placental antigens, were clonally expanded. The population size of clonally expanded CD8+ EM cells was higher in the decidua than in the peripheral blood. CD8+ EM cells began to express PD-1 during the course of normal pregnancy. We found that the total proportion of decidual CD8+ EM cells not expressing PD-1 was increased both in miscarriage and in preeclampsia cases, although a different mechanism was responsible for this increase. The amount of cytotoxic CD8+ EM cells increased in cases of miscarriage, whereas the expression of PD-1 in clonally expanded CD8+ EM cells was downregulated in preeclampsia cases. These results demonstrated that decidual CD8+ EM cells were able to recognize fetal-specific antigens at the feto-maternal interface and could easily induce fetal rejection.